A comparative study of the structural analysis between the integral and the simply supported bridge / Mohd Ashaari Masrom - Masrom, Mohd Ashaari (Universiti Teknologi MARA Pulau Pinang, 2014)
Most bridges in Malaysia have been constructed by using simply supported spans incorporating joints and bearings. As a result, deck expansion joints over every pier and abutment are common features. These expansion joints become the main components that need regular maintenance and replacement. Consequently, the cost to build and maintain such a bridge is expensive in the long run. It is therefore apparent that in future, single and multiple span bridges in this country will be required to be designed as integral bridges with full continuity. This will invariably minimize the maintenance problems and cost, and optimize the use of funds for bridge construction. In relation to that, structural analysis is crucial in designing those bridges. This paper focuses on the structural analysis comparison between integral and simply supported bridges. It was found that the bending moment and displacement of girder in simply supported bridge is always greater than in an integral bridge at the critical point (mid-span). In contrast, the shear force developed in an integral bridge is greater than in a simply supported bridge. The differences in the structural analysis result will produce different specifications of design and detailing in those bridges of similar length bridge span which will then influence the cost of construction.